Postdural puncture headache in the obstetric population: a new approach? - Xavier, João Manuel (2020)
The gold standard for the treatment of postdural puncture headache (PDPH) is the epidural blood patch (EBP). Regional techniques-sphenopalatine ganglion block (SPGB), greater occipital nerve block (GONB) and trigger point infiltration (TPI)-can also be used for the treatment of PDPH. Our objective was to evaluate the efficacy of these peripheral nerve blocks (PNBs) in the treatment of PDPH.